„Błogosławieństwo Judy” (Rdz 49, 8-12) w interpretacji św. Ambrożego z Mediolanu i Rufina z Akwilei - Jóźwiak, Magdalena Małgorzata (Vox Patrum, 2025)
The Book of Genesis 49:1‐28 presents a scene that takes place at Jacob’s deathbed. Before his death, the Patriarch called all his sons to himself to bless them. In biblical studies, this chapter from the Book of Genesis is called “the blessing of Jacob”. One of the sons that Patriarch Jacob blesses is Judah. The subject of this article is to analyze the “blessing of Judah” (Genesis 49:8‐12) as interpreted by St. Ambrose of Milan (cf. Ambrosius, De Patriarchis IV 16‐25) and Rufinus of Aquileia (cf. Rufinus, Rescripta ad Presbyterum Paulinum de Iudae Benedictionibus I 1‐4; De benedictionibus Patriarcharum I 5‐11). In conclusion, Rufinus’ commentary on the “blessing of Judah” is longer, more detailed. Both exegetes draw on Jewish traditions and literal and allegorical interpretations. Both commentators also prefer the model of typical interpretation, hence Judah is for them a “type” of Jesus Christ, his suffering and resurrection.